Pelatihan Pembuatan Pakan Alami Maggot BSF (Hermetia Illucens) Untuk Pakan Budidaya Ikan Sebagai Bentuk Pengabdian Kepada Masyarakat di Desa Tugalagawu, Kecamatan Sirombu, Kabupaten Nias Barat - Enjel Delahowuhowu Telaumbanua; Alfriend John Saotama Halawa; Rosmawati Gea; Rosevelt Cerdas Lase; Cindy Ardita Telaumbanua; Vebriman Jaya Halawa; Destriman Laoli (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
A major problem in the fisheries sector in rural areas is the high cost of fish feed, which can reach 60-70% of total production costs. Training on making natural feed based on Black Soldier Fly (BSF) maggot is an innovative solution in reducing dependence on commercial feed. This community service activity was carried out in Tugalagawu Village, Sirombu District, West Nias Regency using a participatory approach. Activities involved lectures, discussions, and hands-on practice regarding maggot cultivation and its utilization as an alternative fish feed. The results of the training showed an increase in community knowledge and skills in maggot farming, as well as increased enthusiasm in adopting the technology to improve the efficiency of farmed fish production. The training also had a positive impact on household organic waste management and encouraged the economic independence of local communities.